2022
DOI: 10.3389/fpsyt.2022.959467
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, cognitive fusion, and self-compassion in patients with schizophrenia spectrum disorders—A cross-sectional study

Abstract: In the last decades, third wave approaches in cognitive-behavioral therapies (CBT) have shown effectiveness in treating several mental disorders, including schizophrenia spectrum disorders (SSD). Three crucial processes associated with clinical changes in patients include mindfulness, psychological flexibility (PF) and self-compassion (SC). PF is generally assessed by cognitive fusion (CF), a negative formulated key process of PF. The current study encompasses a cross-sectional design to examine the interplay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 101 publications
4
10
0
Order By: Relevance
“…For example, CF was found to predict next-day mindful awareness in a study by Berghoff et al (2018) [33], and mindfulness was found to be the mediator between PF and symptoms of depression in a study by Curtiss & Klemanski (2914) [83]. Furthermore, although recruitment site was included as a covariate in the statistical design, similar to the studies by Bergmann et al (2021) [21] and Böge et al (2022) [24], the medication regime, the understanding of the concept of mindfulness, and already existing experiences should be examined in future trials within a longitudinal design.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, CF was found to predict next-day mindful awareness in a study by Berghoff et al (2018) [33], and mindfulness was found to be the mediator between PF and symptoms of depression in a study by Curtiss & Klemanski (2914) [83]. Furthermore, although recruitment site was included as a covariate in the statistical design, similar to the studies by Bergmann et al (2021) [21] and Böge et al (2022) [24], the medication regime, the understanding of the concept of mindfulness, and already existing experiences should be examined in future trials within a longitudinal design.…”
Section: Discussionmentioning
confidence: 80%
“…Shapiro et al (2006) [23] claim that improving cognitive, emotional, and behavioural exibility might be one mechanism through which mindfulness exerts its positive effects. In recent years, psychological exibility (PF) was often associated with clinical change within the mindfulness framework [24]. PF can be de ned as the ability to consciously interact with the present moment in an accepting way, driven by chosen values and longterm goals rather than distressing internal experiences [25].…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons for the stigma reduction observed in this study include: (a) Cognitive Functioning Enhancement: Mindfulness therapy may positively impact cognitive functioning by enhancing self and metacognition, challenging misconceptions about mental illness, and fostering acceptance of the reality of the condition. This, in turn, empowers patients to confront stigma more effectively, boosting confidence and treatment adherence [ 35 , 36 ]. (b) Attention Control: Mindfulness therapy might enhance patients’ attentional control, fostering a positive understanding of the surrounding environment and mitigating the negative impact of social opinions.…”
Section: Discussionmentioning
confidence: 99%
“…In their meta-analytic review, Bailey et al (2018) showed that CSA was linked to more severe hallucinations, delusions and other positive symptoms of psychosis, though not negative symptoms. Recent research on those with psychosis has shown that self-compassion moderates cognitive fusion as a mediator between mindfulness and negative symptom severity but not total symptom severity (Böge et al, 2022). CSA in psychosis is also linked to poor functioning (Aas et al, 2016), depression, suicidal thoughts and anxiety (Turner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%